Effects of tapering on physical match activities in professional soccer players. Issue 24 (16th December 2016) - Fessi, Mohamed Saifeddin; Zarrouk, Nidhal; Di Salvo, Valter; Filetti, Cristoforo; Barker, Alan R.; Moalla, Wassim
ABSTRACT: This study aimed to examine: (i) the effect of decreasing training load (TL) during taper weeks on physical match activities in professional soccer players, and (ii) to disclose the relationship between weekly TL and physical match activities. Rating of perceived exertion was collected after each training session and match to quantify the TL in 19 professional players over 17 standard and 7 taper weeks during the season. Physical match activities were quantified by a computerised match analysis system and compared between standard training and taper weeks. Compared to standard weeks, the duration and frequency of training sessions during the taper weeks decreased (−21.7% and −18.8%, respectively; P < 0.01) with no change in intensity (−4.8%; P = 0.09). Consequently, the weekly TL decreased during the taper weeks (−25.5%; P < 0.01). Increases in distance covered by intense running (+15.1%; P < 0.05), high-intensity running (HIR) (+15.7%; P < 0.01), number of sprints (+17.8%; P < 0.05) and number of high-speed runs (+15.7%; P < 0.05) were observed during the seven matches played after the taper weeks. High relationships were observed between TL and HIR distance covered, number of HIR and number of sprints ( r = −0.53; r = −0.55; r = −0.65, respectively; P < 0.01). Decreasing TL during taper weeks by reducing training duration and frequency but maintaining intensity was associated with an increase in physical activities during matches. However, it needs to be determined whether tapering or other match factors led to the changes in match activity.